Enhanced Circular Dichroism by F-Type Chiral Metal Nanostructures - Yuyuan Luo; Jin Liu; Haima Yang; Haishan Liu; Guohui Zeng; Bo Huang (Photonics, 2023)
Circular dichroism (CD) effects have broad applications in fields including biophysical analysis, analytical chemistry, nanoscale imaging, and nanosensor design. Herein, a novel design of a tilted F-type chiral metal nanostructure composed of circular nanoholes with varying radii has been proposed to achieve remarkable CD effects, and the results demonstrate the generation of a significant current oscillation at the sharp edges where the nanoholes overlap under circularly polarized light, resulting in a strong CD effect. The CD effect can reach up to 7.5%. Furthermore, spectral modulation of the resonant wavelength can be achieved by adjusting the structural parameters, which enhances the tunability of the structure. Overall, these results provide theoretical or practical guidance for enhancing the circular dichroism signal strength of chiral metal nanostructures and designing new types of two-dimensional chiral structures.